Volume 5A: 41st Mechanisms and Robotics Conference 2017
DOI: 10.1115/detc2017-67947
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Passive and Slope Adaptable Prosthetic Foot

Abstract: Historically, users of prosthetic ankles have relied on actively operated systems to provide effective slope adaptability. However, there are many drawbacks to these systems. This research builds upon work previously completed by Hansen et al. as it develops a passive, hydraulically operated prosthetic ankle with the capability of adapting to varying terrain in every step. Using gait cycle data and an analysis of ground reaction forces, the team determined that weight activation was the most effective way to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Their experiments showed that the subjects felt less fatigued when using the prototype. Very recently, Amiot et al 9 developed a passive hydraulic design ( Figure 4) for a prosthetic ankle as a proof of concept. Their design allowed the ankle to change foot angles according to the slopes.…”
Section: Survey Passive Lower Limb Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their experiments showed that the subjects felt less fatigued when using the prototype. Very recently, Amiot et al 9 developed a passive hydraulic design ( Figure 4) for a prosthetic ankle as a proof of concept. Their design allowed the ankle to change foot angles according to the slopes.…”
Section: Survey Passive Lower Limb Prosthesesmentioning
confidence: 99%
“…Similar to, 8 Amiot et al 9 used a flexible foot to make their version of the ankle slope adaptable. Their use of hydraulic components in the system is just like.…”
Section: Passive Lower Limb Prosthesesmentioning
confidence: 99%
“…The clutch mechanism can be either purely mechanical (often weight-activated) or electromechanical in nature (microcontroller-activated based upon sensor signals). Several research prototypes utilize this design approach (Nickel et al, 2014 ; Amiot et al, 2017 ; Holgate et al, 2017 ; Lee et al, 2017 ; Heremans et al, 2019 ). These clutch-based devices are typically intended to also adapt to varying ground slopes, and as such, are typically heavier and more complex than is necessary to solely achieve the swing phase dorsiflexion functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide slope adaptation, some researchers have developed passive devices that alter the ankle stiffness set-point as a function of ground slope [37][38][39]. These devices incorporate mechanical or hydraulic locking mechanisms to lock the ankle joint at various ankle angles as a function of ground slope.…”
Section: Introductionmentioning
confidence: 99%